Targeting XIAP-coordinated PKC signaling resensitizes PD-1-refractory tumors for rechallenge - Jupeng Yuan; Yujiao Ma; Ying Dong; Zengfu Zhang; Yuequn Ma; Fei Wang; Baoqing Tian; Ying Xu; Xiaoliang Wang; Xu Liu; Hanghang Yuan; Mei Liu; et al. (Proceedings of the National Academy of Sciences, 2026)
Despite revolutionizing oncology, PD-1/PD-L1-directed immune-checkpoint blockade (ICB) is limited by primary or acquired resistance that is routinely countered—without mechanistic clarity—by empiric rechallenge. Here, we identify substrate-based protein kinase C (PKC) activity as a prognostic biomarker in non-small cell lung cancer and a therapeutic target in anti-PD-1-refractory tumors. Pan-PKC inhibition overcomes anti-PD-1 resistance by inducing Caspase-3/GSDME-dependent immunogenic pyroptotic cell death, promoting tumor-intrinsic PD-L1 degradation via GSK3β activation, and enhancing CD8 + T cell recruitment and effector function through tumor-derived CCL4–CCR5 signaling. Mechanistically, PKC blockade destabilizes XIAP, relieving caspase inhibition, stabilizing PTEN, and suppressing Wnt/β-Catenin-ATF3 signaling to drive CCL4 expression. In resistant models, PKC inhibition synergizes more effectively with anti-CTLA-4 than with anti-PD-1/PD-L1, in association with reduced intratumoral regulatory T cells and reinforcement of CD8 + T cell effector function. These findings define the PKC–XIAP axis as a central regulator of immune resistance and provide a mechanistic rationale for PKC inhibition plus anti-CTLA-4 as a salvage strategy in ICB-refractory cancers.